Elliptical Annular Slot Loaded Trapezoidal Dipole Antenna for Band-Notched UWB Applications - Singh, Amit Kumar; Verma, Nand Kishor (Iraqi Journal for Electrical and Electronic Engineering, 2016)
In this paper, a semi-elliptical annular slot loaded trapezoidal dipole antenna with band-notched characteristics for UWB applications is designed. A microstrip feedline consisting of multiple feedline sections is used for improving the impedance matching. The band-notched characteristics for WLAN band are achieved by loading the trapezoidal dipole arms with semi- elliptical annular slots. The designed antenna structure has an operating range from 3.5-12.4 GHz(109%) with band-rejection in the frequency range of 5-6 GHz. Nearly omnidirectional patterns are achieved for the designed antenna structure. The designed antenna structure provided an average peak gain of 2.12 dB over the entire frequency range except in the notched band where it reduced to -2.4 dB. The experimental and simulation results are observed to be in good agreement. An improved bandwidth performance with miniaturized dimensions as compared to earlier reported antenna structures is achieved.